Karakterisasi Fisik, Kimia dan Fraksi Protein 7S dan 11S Sepuluh Varietas Kedelai Produksi Indonesia - Yuwono, Sudarminto Setyo; Hayati, Kartika Ken; Wulan, Siti Narsito (Jurnal Teknologi Pertanian, 2003)
Efforts to develop new varieties of soybeans had been carried out to produce a better quality of yield. Variety of soybeans would affect on properties of products. Besides the chemical compositition, properties of the product may be caused by content of protein globulin fraction such as 7S and 11S. Results showed that some soybean varieties have a higher chemical properties such as protein content compared to imported soybean from USA. Fat, protein, ash and carbohydrate content were 18,539-22,57%; 30,32-35,35%; 5,53-5,96%; 36,83-43,93% respectively, whereas imported soybean contained 22,97%, 31,06%, 5,62%, 40,35% respectively. Globulin 7S and 11S of the samples ranged from 4, 48-14, 05%, and 7,32 - 56,82% respectively. Imported soybean contained globulin 7S 10,44% dan 11S 53,45%. Variey of Lompobatang and Davros contained globulin 11S higher than that imported soybean. Keywords : soybean, fractionation, globulin protein